An electrochemical-thermal coupling model for heat generation analysis of prismatic lithium battery. (June 2022) - Ren, Honglei; Jia, Li; Dang, Chao; Qi, Zhuoling
Abstract: In this study, an electrochemical thermal coupling model of prismatic lithium battery was established to simulate the actual discharge process. The heat generation distribution and variation in porous electrodes and current collectors were analyzed and the relationship among the total heat generation, discharge rate and discharge time was proposed. The simulation result indicated that the heat generation distribution in the porous electrodes was non-uniform. The moving distance of the peak heat generation density became shorter with the increase of discharge rate. The heat generation density increased with the discharge time. In the porous area, the negative electrode was dominant, and the proportion of polarization heat was the highest. The heat generation of battery was non-uniformity distributed on the current collectors, which increased with the discharge rate and decreased with the progress of discharge. The heat generation expression proposed in this paper could accurately predict the relationship between the total heat generation and the discharge time under each discharge rate, which could provide theoretical support for the establishment of a battery thermal management system. Highlights: The heat generation distribution in porous electrodes and current collectors were analyzed. Relational formula of the total heat generation, discharge rate and discharge time was proposed. The heat generation of battery was non-uniformity distributed on the current collectors.